The genome sequence of the Streamer, Anticlea derivata (Denis & Schiffermüller, 1775) - Boyes, D; Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual female Anticlea derivata (the Streamer; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence is 355.8 megabases in span. Most of the assembly is scaffolded into 32 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 17.39 kilobases in length.